THE IMPROVEMENT OF STUDENTS’ HIGHER ORDER THINKING IN READING CLASS USING STUDENTS’ RESPONSES TEXTS IN THE THIRD SEMESTER OF ENGLISH EDUCATION PROGRAM PGRI UNIVERSITY OF YOGYAKARTA - Sri Wiyanah (Journal of English Language Teaching and English Linguistics, 2014)
The research aims to improve the level thinking qualities toward students in Reading III using students‘ responses text. The research applied descriptive qualitative method. It described about the students‘ responses text that produced by students in reading novel to improve students‘ higher order based on their own perspective. The participants of this research were nine students of the semester III, A3 class, English Education Program of PGRI University of Yogyakarta. Data were got through observation, interview, document analysis and questionaire. Qualitative data were anayzed through coding data, explanation, or data presenting and conclusion. The findings showed that using students‘ responses text in Reading III learning process that focus on novel significantly improve the students‘higher order thinking level. The first activities, students‘order thinking level still in the lower category i.e., remember and understand. The precentage is only 25%. The second activities, students‘order thinking level imrpoved up to 45%. The improvement of students‘order thinking in reading comprehension using students‘ responses also influenced students‘ motivation and feeling when they were learning. The response text helped students in improving their reading skill.